PENERAPAN STRATEGI BELAJAR AKTIF LEARNING START WITH A QUESTION (LSQ) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 10 PEKANBARU - Ayuningtyas, Putry Ayuningtyas Putry; ', Herdini; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT Research on the application of active learning strategy type Learning Start With A Question (LSQ)) has been done to improve student’s achievement on the subject of hydrocarbon in class X of SMAN 10 Pekanbaru. Form of the research is experiment research with pretest-posttest design. The sample consisted of two classes, X.5 class as experiment class and X.7 class as control class that randomly selected after testing normality and homogeneity. Experiment class was given by implementing active learning strategy type LSQ and the control class was given by conventional method. Analysis of data used t-test. Data of research obtained tcount > ttable (5,78 > 1,67). It means that using active learning strategy type LSQ can improve student’s achievement on the subject of hydrocarbon in class X of SMAN 10 Pekanbaru. The category improvement of student’s achievement in experiment class was high category (N-Gain =0,71) and in control class was medium category (N-Gain =0,51). Keywords : Active Learning Strategy, Learning Start With A Question (LSQ), Student’s Achievement, Hydrocarbon